Invasive zygomycosis in India: experience in a tertiary care hospital. Issue 1009 (5th November 2009) - Chakrabarti, A; Chatterjee, S S; Das, A; Panda, N; Shivaprakash, M R; Kaur, A; Varma, S C; Singhi, S; Bhansali, A; Sakhuja, V
Abstract : Aim: To report the natural history and clinical course of zygomycosis from a single tertiary care centre in India where doctors maintain an institutional zygomycosis registry. Methods: The clinical and laboratory data collected prospectively from patients with antemortem diagnosis for invasive zygomycosis, and retrospectively from autopsy diagnosed cases, over an 18 month period (July 2006–December 2007) were combined and analysed. Results: During the period 75 cases (50 cases/year) of zygomycosis were reported. Antemortem diagnosis could be made in 81% of cases and 9% of patients had nosocomial zygomycosis. The spectrum of disease included rhino-orbito-cerebral (48%), pulmonary (17%), gastrointestinal (13%), cutaneous (11%), renal and disseminated zygomycosis (5% each). Uncontrolled type 2 diabetes (58%) and diabetic ketoacidosis (38%) in the rhino-orbito-cerebral type, renal failure (69%) in the pulmonary type, prematurity (70%) in the gastrointestinal type, and breach of skin (88%) in cutaneous zygomycosis, were the significant (p<0.05) underlying illnesses. Rhizopus oryzae (69%) was the most common isolate followed by Apophysomyces elegans (19%). Overall mortality was 45% in patients who could be treated. Outcome was significantly poor when surgical debridement could not be performed or the patients were treated only with amphotericin B deoxycholate. On multivariate analysis, patients with a Glasgow Coma Score (GCS) ⩾9 had a better prognosis. Conclusions: Zygomycosis is a threat in uncontrolled diabetes. New risk factors such as renal failure and chronic liver disease require attention. A elegans is an emerging agent in India. The need for surgical debridement in addition to medical treatment is emphasised. GCS is an independent marker of prognosis in cases of invasive zygomycosis.